Natural selection and the evolution of life expectancy - Oded Galor; Omer Moav (Brown University, Department of Economics, 2004)
This research develops an evolutionary growth theory that captures the intricate time path of life expectancy in the process of development, shedding new light on the origin of the remarkable rise in life expectancy since the Agricultural Revolution. The theory argues that social, economic and environmental changes that were associated with the transition from hunter-gatherer tribes to sedentary agricultural communities and ultimately to urban societies affected the nature of the environmental hazards confronted by the human population, triggering an evolutionary process that had a significant impact on the time path of human longevity.
Keywords: I12; J13; N3; O10; 330; Life Expectancy; Growth; Technological Progress; Evolution; Natural Selection; Malthusian Stagnation; Evolutionsökonomik; Wirtschaftswachstum; Sterblichkeit; Technischer Fortschritt; Bioökonomik; Bevölkerungstheorie